Role of HIF-1, Siah-1 and SKN-1 in Inducing Adiposity for Caenorhabditis elegans under Hypoxic Conditions - I Gede Widhiantara; Anak Agung Ayu Putri Permatasari; I Wayan Rosiana; I Wayan Putu Sutirtayasa; Ferbian Milas Siswanto (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Hypoxia has been shown to be able to induce adiposity. However, the mechanism and factors involved in this effect still remains unclear. Hence, we sought to investigate the role of oxygensensitive factors regarding hypoxia-induced adiposity in nematode Caenorhabditis elegans.METHODS: The C. elegans were grown on nematode growth medium (NGM) agar plates seeded with Escherichia coli OP50 at 20°C. The ratio of width/body length was measured using the morphometry analysis. Fat accumulation was examined using Sudan Black methods. Protein levels of sterol binding protein (SBP)-1 were assessed by immunoblotting. Lifespan assay was performed at 20°C and was monitored every two days.RESULTS: The results showed that of all mutant used, only hif-1 mutant which did not experience an increase in the ratio of width/body length (p>0.05) and fat accumulation (p>0.05), indicating that hypoxia-inducible factors (HIF)-1 plays an important role in the pathogenesis of hypoxia-induced adiposity. Both siah-1 and skn-1 mutants experienced SBP-1 protein elevation (p<0.05), and increased fat-6 mRNA expression (p<0.05) which were not experienced by a hif-1 mutant (p>0.05) further supporting that HIF-1 acts as an upstream regulator fromSBP-1.CONCLUSION: In general, the results of this study provide evidences of the involvement of the transcription factor HIF-1 in inducing adiposity under the hypoxic conditions. However, we did not find the involvement of seven in absentia homolog-1 (Siah-1) and skinhead-1 (SKN-1).KEYWORDS: hypoxia, adiposity, fat, HIF-1, Siah-1, SKN-1, C. elegans